Application of Billing Pos (point of Sales) on Cloud Computing for Restaurant by Using IoT (internet of Things) Device with Data Synchronized Method in The Reporting Process - R Dimas Adityo; Herti Miawarni (JEECS (Journal of Electrical Engineering and Computer Sciences), 2018)
In this study POS (Point Of Sales) Billing System was designed and built with more affordable prices onRestaurant Taxpayers using IoT (Internet Of Thing) devices by utilizing Cloud Computing technology that cansending sales report data in realtime to the server owned by the Probolinggo Regency Financial and AssetAgency. The input from this study is data that is sent in realtime from a billing machine, from a series of tests thathave been carried out that can run smoothly, that is proven by measuring data transmission with speed inaccessing article data an average of 0.7833 seconds / data transactions compared manually. So that through thisapplication, estimates of regional revenue targets can be monitored directly.